Analisis Garapan Tari Sanggar Seni Sarai Sarumpun Di Kota Padang - Nur Na’afi Putri; Darmawati Darmawati (SENDRATASIK UNP, 2021)
This research aims to find out the dance work of Sarai Sarumpun Art workshops in Padang City. This type of research is qualitative research, and the method used is a description of the analysis. The instruments in this study are the researchers themselves and assisted with supporting instruments such as stationery and mobile phones. The data type uses primary data and secondary data. Data collection techniques are carried out by library studies, observations, interviews, recording and shooting. The steps for analyzing the data are data reduction, data presentation and withdrawal of conclusions. The results showed that the dance work of Sarai Sarumpun Art workshops seen in his three dances is Hoyak Badarai Plate dance, Indang Sarumpun dance, Rampak Nuri Shawl dance. Of these three dances found the wiggle room is dominated by large wiggle room, and the time of movement implementation is dominated by medium time, as well as the use of energy in motion dominated by medium-sized energy. More dance moves are used in curved zig-zag line patterns that produce emotional touches full of feeling (joy). Thus the supporting elements such as the joyous sense of music presented by the variety of sounds and costumes with colorful and varied floor patterns that all reinforce the joyous atmosphere that is presented in the dance of entertainment.